CROSSFIT AS AN INNOVATIVE SYSTEM OF PHYSICAL EDUCATION FOR STUDENTS OF THE MINISTRY OF INTERNAL AFFAIRS OF THE REPUBLIC OF UZBEKISTAN - Albekov Shokir Adilbekovich (Proximus Journal Publishing, 2023)
Innovation is an implemented innovation that provides a qualitative increase in the efficiency of processes or products that are in demand by the market. It is the end result of a person's intellectual activity, his imagination, creative process, discoveries, inventions and rationalization
Keywords: functional all-around; crossfit; innovation; physical education